Data for: Overwintering fires can occur in both peatlands and upland forests with varying ecological impacts ... - Baltzer, Jennifer L.; Veraverbeke, Sander; Hessilt, Thomas D.; Alfaro Sánchez, Raquel; Van Gerrevink, Max J.; Ogden, Emily L.; Olsen, Richard; Scholten, Rebecca C.; Turetsky, Merritt R. (Borealis, 2025)
This dataset is original data from overwintering and single season fires in the Northwest Territories, Canada. It includes species-specific pre- and post-fire tree stem density estimates, stand structural data, and above and belowground combustion data for sites that burned in 2014 (single season fires), some of which continued to burn through the winter, reignite in the spring and reburn in the 2015 fire season (overwintering fires). In each region, we sampled adjacent overwintering and single-season burn sites. We used previous detections of overwintering fires based on satellite data and reports from fire managers to identify overwintering fires and increased the accuracy of overwintering fire locations using 30m Landsat imagery. Adjacent to these overwintering sites, we identified single-season burn sites from within portions of the 2014 fires that were unaffected by overwintering. The identified single-season sampling location was also evaluated on the ground to ensure comparability in site attributes ... : This is the manuscript associated with this dataset. ...